Yield, biomass composition, and N use efficiency during establishment of four Miscanthus × giganteus genotypes as influenced by N management. (August 2016) - Dierking, R.M.; Allen, D.J.; Brouder, S.M.; Volenec, J.J.
Abstract: Few studies have examined N management strategies to accelerate Miscanthus establishment. Our objectives were: (i) determine differences in biomass yield among various M . × giganteus genotypes as influenced by N management during establishment; (ii) quantify the impact of genotype and N management on biomass composition; and (iii) determine how M . × giganteus genotype and N management influence nitrogen use efficiency (NUE). Four M . × giganteus genotypes were planted near Schochoh, KY and Lafayette, IN in 2010. A two-year total N application of 150 kg ha −1 was applied using various combinations of 50, 75, and 100 kg ha −1 y −1 . Control N rates included 0 and 150 kg ha −1 each year. Yield, composition, and NUE of the MS and IL clones were similar. Two-year cumulative yields of Nagara were higher than the other genotypes in KY, and the IL clone in IN. There was no response of yield to N on the silt loam soil in KY, whereas high biomass yields were achieved with 50 kg ha −1 y −1 of N on the sandy loam soil in IN. Yields of plots provided high N in Season 1 were similar to unfertilized control plots in Season 2 suggesting little N carryover from Season 1 to 2. Biomass fiber concentrations were not influenced by N-fertilization, but high leaf retention of the Nagara lines reduced biomass cellulose and lignin concentrations. Site-specific genotypic differences in NUE were observed. Annual N applications of 50 kg ha −1 is recommended to enhanced Miscanthus yield during establishment on the coarse-textured soils. Highlights: 50 kg ha −1 of N was adequate to facilitate establishment. There was no evidence of N carryover in Season 1 of establishment to enhance Season 2 growth. Genotypic differences in composition and NUE were associated with leaf retention.